2017
DOI: 10.1002/mc.22671
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group A1 enhances tumorigenicity of human cholangiocarcinoma and confers resistance to therapy

Abstract: High mobility group A1 (HMGA1) protein has been described to play an important role in numerous types of human carcinoma. By the modulation of several target genes HMGA1 promotes proliferation and epithelial-mesenchymal transition of tumor cells. However, its role in cholangiocarcinoma (CCA) has not been addressed yet. Therefore, we determined HMGA1 mRNA expression in CCA samples in a transcriptome array (n = 104) and a smaller cohort (n = 13) by qRT-PCR. Protein expression was evaluated by immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Finally, activation of EMT is also involved in resistance to chemotherapy (MOC-7) 366 . High mobility group A1 protein promoted CCA tumorigenicity and conferred resistance to gemcitabine in vitro in CCA cell lines 388 .…”
Section: Mechanisms Of Chemoresistance (Moc) Accounting Formentioning
confidence: 98%
“…Finally, activation of EMT is also involved in resistance to chemotherapy (MOC-7) 366 . High mobility group A1 protein promoted CCA tumorigenicity and conferred resistance to gemcitabine in vitro in CCA cell lines 388 .…”
Section: Mechanisms Of Chemoresistance (Moc) Accounting Formentioning
confidence: 98%
“…Recent studies have revealed that IL-17 overproduction contributes to the inflammatory microenvironment for NSCLC cell proliferation and growth (5,11). Moreover, HMGA1 as a transcription factor and cyclin D1 as a proliferative protein can also promote cancer cell proliferation (40)(41)(42)(43). Hence, in this study, in order to better understand the pathogenesis of IL-17-induced NSCLC cell proliferation, we first detected the level of IL-17 in plasma, and the expression of IL-17R, HMGA1 as well as that of cyclin D1 in the tumor tissues of patients with NSCLC.…”
Section: Disscussionmentioning
confidence: 99%
“…Reportedly, HMGA1 protein acts within the nucleus of mammalian cells as an architectural transcription factor (40,42); however, the cytoplasmic/mitochondrial localization of HMGA1 protein in multiple cell types has also been found (35), suggesting that HMGA1 may undergo nucleocytoplasmic translocation during some biological processes. Moreover, HMGA1 can modulate gene expression by altering the chromatin structure and orchestrating the assembly of transcription factor complexes to augment target gene promoter activity (42).…”
Section: Disscussionmentioning
confidence: 99%
“…Notably, increased expression of HMGA1 signi cantly correlated with the malignant status and prognosis of NSCLC [11]. Interestingly, although it is not lung cancer, recent studies have shown that increased expression of HMGA1 is closely related to the recurrence of various cancers, like hepatocellular carcinoma [12], cholangiocarcinoma [13], and acute lymphoblastic leukemia [14], indicating that elevated HMGA1 plays an important role in cancer recurrence. Together, these ndings suggest that elevated HMGA1 may be involved in the progression of early-stage lung cancer.…”
Section: Introductionmentioning
confidence: 99%